Impact of two different body mass management strategies on repeated rowing performance - Slater, G. J.; Rice, A. J.; Tanner, R.; Sharpe, K.; Jenkins, D.; Hahn, A. G. (Medicine & Science in Sports & Exercise, 2006)
Purpose: The present study was conducted to examine the impact of acute weight loss on repeat 2000-m rowing ergometer performance during a simulated multiday regatta, and to compare two different body mass management strategies between races.